Governance of marine protected areas in the least-developed countries : Case studies from West Africa - (:unkn) unknown (My University, 2011)
The need for effective governance of the marine protected areas (MPAs) in least developed countries (LDCs) is commensurate with the significant territorial stakes raised by their extensive maritime domain. Another significant challenge is the conservation of biodiversity and of ecosystems whose level of productivity is similar to that of coral reefs (e.g. in East Africa and Madagascar, the Red Sea, Maldives, Cambodia, and South Pacific islands), upwelling systems (e.g. in West Africa and Angola) and estuarine and delta ecosystems (e.g. in West and East Africa, Bangladesh and Myanmar). However, the overriding issue is to reconcile conservation and human presence as, in LDCs, human activities are tolerated in almost all MPAs covered by International Union for Conservation of Nature categories II-VI. Finally, issues related to identity claims and to the process of establishment of property and other legal entitlements on nature are gaining importance. A review of the literature on fisheries and MPAs governance showed how polysemous and vague the notion of governance was until very recently and how few or oversimplified were the analyses of MPA governance in the LDCs. However, only detailed analyses would allow the characterization of governance systems and identification of their weaknesses with the view to suggesting new governance arrangements and appropriate public policy options. Such analytical deficiencies may be explained by the lack of analytical frameworks capable of taking into account the plurality and intricacy of socio-economic organizations and institutions, the sociocultural features and the role of new mediators and "development brokers" that shape MPA governance in the LDCs. The deficiencies may also be explained by the fact that the dominating hierarchical governancesystems tend to underestimate the complexity of MPA governance systems. Therefore, it has been necessary to develop an analytical framework to study the governance of MPAs in
Keywords: African Research